When to become an electronic business venture after the COVID-19 pandemic? The role of strategic orientation and perceived environmental turbulence in determining online market entry timing - Mao, Hongyi; He, Changqing; Huang, Xing; Wu, Banggang; Chen, Zhi; Zhou, Liying (Frontiers in Public Health, 2022)
After the COVID-19 epidemic, a growing number of commercial entities have decided to enter the online platform and operated as an electronic business venture. However, the timing of entering the online market is a strategically important issue. On the basis of social capital theory and resource-based view, this study attempts to understand the different impacts of two strategic orientations (i.e., Guanxi orientation and entrepreneurial orientation) and perceived environmental turbulence (i.e., market turbulence and political turbulence) on online market entry timing. We test four hypotheses using data collected from 174 Chinese companies. Our results confirm that entrepreneurial orientation negatively impacts online market entry timing, and this effect is moderated by perceived market turbulence such that the negative relationship between entrepreneurial orientation and online market entry timing will be strengthened in higher market turbulence. By contrast, Guanxi orientation positively impacts online market entry timing, and the positive relationship between Guanxi orientation and online market entry timing will be weakened in higher political turbulence. Implications and future research directions are discussed.